Fish welfare in a changing world: New developments and current challenges - Sonia Rey Planellas; João L. Saraiva; Eliane Gonçalves‐de‐Freitas; Pablo Arechavala‐Lopez; Bernice Bovenkerk; Michael Breen; Steven J. Cooke; Martin Føre; Lene Northwood; Lars Helge Stien; Sunil Kadri; Chris Noble; et al. (Journal of Fish Biology, 2026)
The welfare of non‐human animals is central to ethical discussions on animal use, with increasing attention to fish welfare across research, aquaria, aquaculture, and fisheries. This paper reviews current theoretical approaches to animal welfare and recent advances in defining and assessing fish welfare since the seminal paper by Huntingford et al. (2006; J Fish Biol 68 : 332–372), highlighting the growing role of cognitive and affective processes. It also includes the concept of positive welfare and some of the current research advances in this field. Methods for measuring, monitoring and assessing welfare via the utilisation of outcome‐ and input‐based indicators are outlined, ranging from practical operational tools to laboratory‐based measures. Welfare concerns in wild‐capture fisheries are examined in relation to stress, flesh quality and sustainability, including the welfare of released fish. Recent advances in fish neurobiology, cognition and pain perception are summarised, together with technological innovations that enhance welfare monitoring and management. The paper also explores the relationship between fish welfare, sustainability, public concerns and consumer demand, and legal and moral recognition across contexts, situating fish welfare within the ‘One Health’ and ‘One Welfare’ frameworks that link animal welfare, environmental stewardship and human well‐being. Ongoing challenges include climate change, cultural factors and the interpretation of fish sentience and cognition among others.

Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

P19-19 Application of InSight™ human 3D MASLD/MASH spheroid models for DILI assessment of compounds - P. Vonschallen; A. Pawlowska; B. Filippi; L. Fäs; T. Hofstetter; J. Zvick; J. Glaus; A.B. Breen; F. Verdeguer; R. Kostadinova (Toxicology Letters, 2025)

Tundra Plant Canopies Gradually Close Over Three Decades While Cryptogams Persist - Katlyn R. Betway‐May; William A. Gould; Sarah C. Elmendorf; Jeremy L. May; Robert D. Hollister; Steven F. Oberbauer; Amy Breen; Benjamin J. Crain; Ana Maria Sanchez Cuervo; Marilyn D. Walker; Donald A. Walker (Global Change Biology, 2025)
Global climate change phenomena are amplified in Arctic regions, driving rapid changes in the biota. Here, we examine changes in plant community structure over more than 30 years at two sites in arctic Alaska, USA, Imnavait Creek and Toolik Lake, to understand long‐term trends in tundra response to changing climate. Vegetation cover was sampled every 4–7 years on permanent 1 m 2 plots spanning a 1 km 2 grid using a point‐frame. The vascular plant canopies progressively closed at both locations. Canopy cover, defined here as an encounter of a vascular plant above the ground surface, increased from 63% to 91% at Imnavait Creek and from 63% to 89% at Toolik Lake. Both sites showed steady increases in maximum canopy height, increasing by approximately 50% (8 cm). While cover and height increased to some extent for all vascular plant growth forms, deciduous shrubs and graminoids changed the most. For example, at Imnavait Creek the cover of graminoids more than tripled (particularly in wet meadow plots), increasing by 237%. At Toolik Lake the cover of deciduous shrubs more than doubled (particularly in moist acidic plots), increasing by 145%. Despite the steady closing of the plant canopy, cryptogams (lichens and mosses) persisted; in fact, the cover of lichens increased. These results call into question the dominant dogma that cryptogams will decline with increases in vascular plant abundance and demonstrate the resilience of these understory plants. In addition to overall cover, the diversity of vascular plants increased at one site (Imnavait Creek). In contrast to much of the Arctic, summer air temperatures in the Toolik Lake region have not significantly increased over the 30+ year sampling period; however, winter temperatures increased substantially. Changes in vegetation community structure at Imnavait Creek and Toolik Lake are likely the result of winter warming.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Protracted volitional spawning of pinfish Lagodon rhomboides and changes in egg quality and fatty‐acid composition throughout the spawning season - J. S. Broach; C. L. Ohs; N. E. Breen (Journal of Fish Biology, 2017)
Spawning performance of pinfish Lagodon rhomboides without use of hormonal aids was monitored over an extended season. Nearly three million eggs were obtained from 75 spawns collected over a 90‐day consecutive period from a single population of four brood fish (1M:1F). A mean ± s.d. batch fecundity of 30·27 ± 22·64 eggs g −1 female was estimated with 98·0 ± 0·06% of the batch composed of floating eggs which were 1·04 ± 0·04 mm in diameter and 85·71 ± 27·59% fertile. Floating eggs successfully hatched 54·65 ± 29·13% of the time which yielded larvae that were 2·59 ± 0·24 mm in length. Fatty acids within floating eggs were largely represented by polyunsaturated fatty acids (45·30 ± 2·14% of total fatty acids) of which linoleic acid [(c18:2 n‐ 6cis) 3·49 ± 1·69% trifluoroacetic acid (TFA)] and docosahexaenoic acid (DHA) [(c22:6 n‐ 3) 28·47 ± 1·48% TFA] represented the majority of fatty acids for n‐ 6 and n‐ 3 polyunsaturated fatty acids, respectively. The strongest correlations between fatty acids and hatching success and larval survival to first feeding were observed for the DHA:EPA (eicosapentaenoic acid; c20:5 n‐ 3) ratio and total n‐ 6 polyunsaturated fatty‐acids levels, respectively. These data demonstrate potential for producers to rely on natural spawns for extensive egg production and provide a baseline for future development of natural spawning protocols of captive L. rhomboides .

The regional species richness and genetic diversity of A rctic vegetation reflect both past glaciations and current climate - Lærke Stewart; Inger G. Alsos; Christian Bay; Amy L. Breen; Christian Brochmann; Noémie Boulanger‐Lapointe; Olivier Broennimann; Helga Bültmann; Peder Klith Bøcher; Christian Damgaard; Fred J. A. Daniëls; Dorothee Ehrich; et al. (Global Ecology and Biogeography, 2016)
Aim The A rctic has experienced marked climatic differences between glacial and interglacial periods and is now subject to a rapidly warming climate. Knowledge of the effects of historical processes on current patterns of diversity may aid predictions of the responses of vegetation to future climate change. We aim to test whether plant species and genetic diversity patterns are correlated with time since deglaciation at regional and local scales. We also investigate whether species richness is correlated with genetic diversity in vascular plants. Location Circumarctic. Methods We investigated species richness of the vascular plant flora of 21 floristic provinces and examined local species richness in 6215 vegetation plots distributed across the A rctic. We assessed levels of genetic diversity inferred from amplified fragment length polymorphism variation across populations of 23 common A rctic species. Correlations between diversity measures and landscape age (time since deglaciation) as well as variables characterizing current climate were analysed using spatially explicit simultaneous autoregressive models. Results Regional species richness of vascular plants and genetic diversity were correlated with each other, and both showed a positive relationship with landscape age. Plot species richness showed differing responses for vascular plants, bryophytes and lichens. At this finer scale, the richness of vascular plants was not significantly related to landscape age, which had a small effect size compared to the models of bryophyte and lichen richness. Main conclusion Our study suggests that imprints of past glaciations in A rctic vegetation diversity patterns at the regional scale are still detectable today. Since A rctic vegetation is still limited by post‐glacial migration lag, it will most probably also exhibit lags in response to current and future climate change. Our results also suggest that local species richness at the plot scale is more determined by local habitat factors.

A novel canine kidney cell line model for the evaluation of neoplastic development: karyotype evolution associated with spontaneous immortalization and tumorigenicity - R. Omeir; R. Thomas; B. Teferedegne; C. Williams; G. Foseh; J. Macauley; L. Brinster; J. Beren; K. Peden; M. Breen; A. M. Lewis (Chromosome Research, 2015)

US trends in survival disparities among adolescents and young adults with non-Hodgkin lymphoma - Erin E. Kent; Nancy Breen; Denise R. Lewis; Janet S. de Moor; Ashley Wilder Smith; Nita L. Seibel (Cancer Causes & Control, 2015)

Genomics in a changing arctic: critical questions await the molecular ecologist - Stan D. Wullschleger; Amy L. Breen; Colleen M. Iversen; Matthew S. Olson; Torgny Näsholm; Ulrika Ganeteg; Matthew D. Wallenstein; David J. Weston (Molecular Ecology, 2015)
Molecular ecology is poised to tackle a host of interesting questions in the coming years. The Arctic provides a unique and rapidly changing environment with a suite of emerging research needs that can be addressed through genetics and genomics. Here we highlight recent research on boreal and tundra ecosystems and put forth a series of questions related to plant and microbial responses to climate change that can benefit from technologies and analytical approaches contained within the molecular ecologist's toolbox. These questions include understanding (i) the mechanisms of plant acquisition and uptake of N in cold soils, (ii) how these processes are mediated by root traits, (iii) the role played by the plant microbiome in cycling C and nutrients within high‐latitude ecosystems and (iv) plant adaptation to extreme Arctic climates. We highlight how contributions can be made in these areas through studies that target model and nonmodel organisms and emphasize that the sequencing of the Populus and Salix genomes provides a valuable resource for scientific discoveries related to the plant microbiome and plant adaptation in the Arctic. Moreover, there exists an exciting role to play in model development, including incorporating genetic and evolutionary knowledge into ecosystem and Earth System Models. In this regard, the molecular ecologist provides a valuable perspective on plant genetics as a driver for community biodiversity, and how ecological and evolutionary forces govern community dynamics in a rapidly changing climate.

Application of an unmanned aerial vehicle in spatial mapping of terrestrial biology and human disturbance in the McMurdo Dry Valleys, East Antarctica - Barbara Bollard-Breen; John D. Brooks; Matthew R. L. Jones; John Robertson; Sonja Betschart; Olivier Kung; S. Craig Cary; Charles K. Lee; Stephen B. Pointing (Polar Biology, 2015)

Genetic risk score analysis indicates migraine with and without comorbid depression are genetically different disorders - Lannie Ligthart; Jouke-Jan Hottenga; Cathryn M. Lewis; Anne E. Farmer; Ian W. Craig; Gerome Breen; Gonneke Willemsen; Jacqueline M. Vink; Christel M. Middeldorp; Enda M. Byrne; Andrew C. Heath; Pamela A. F. Madden; et al. (Human Genetics, 2014)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

Genetic consequences of glacial survival: the late Quaternary history of balsam poplar ( Populus balsamifera L.) in North America - Amy L. Breen; David F. Murray; Matthew S. Olson (Journal of Biogeography, 2012)
Aim Beringia, the unglaciated region encompassing the former Bering land bridge, as well as the land between the Lena and Mackenzie rivers, is recognized as an important refugium for arctic plants during the last ice age. Compelling palaeobotanical evidence also supports the presence of small populations of boreal trees within Beringia during the Last Glacial Maximum. The occurrence of balsam poplar ( Populus balsamifera ) in Beringia provides a unique opportunity to assess the implications of persistence in a refugium on present‐day genetic diversity for this boreal tree species. Location North America. Methods We sequenced three variable non‐coding regions of the chloroplast genome (cpDNA) from 40 widely distributed populations of balsam poplar across its North American range. We assessed patterns of genetic diversity, geographic structure and historical demography between glaciated and unglaciated regions of the balsam poplar’s range. We also utilized a coalescent model to test for divergence between regions. Results Levels of genetic diversity were consistently greater for populations at the southern margin (θ W = 0.00122) than in the central (θ W = 0.00086) or northern (θ W = 0.00034) regions of the current distribution of balsam poplar, and diversity decreased with increasing latitude ( R 2 = 0.49, P 0.01). We detected low, but significant, structure ( F CT = 0.05, P = 0.05), among regions of P. balsamifera ’s distribution. The cpDNA genealogy was shallow, however, showing an absence of highly differentiated chloroplast haplotypes. Coalescent analyses supported a model of divergence between the southern ice margin and the northern unglaciated region of balsam poplar’s distribution, but analyses of other regional comparisons did not converge. Main conclusions The palaeobotanical record supports the presence of a Beringian refugium for balsam poplar, but we were unable to definitively identify the presence of known refugial populations based on genetic data alone. Balsam poplar populations from Beringia are not a significant reservoir of cpDNA diversity today. Unique alleles that may have been present in the small, isolated populations that survived within Beringia were probably lost through genetic drift or swamped by post‐glacial, northward migration from populations south of the ice sheets.

A multiple resistance locus on chromosome arm 3BS in wheat confers resistance to stem rust (Sr2), leaf rust (Lr27) and powdery mildew - R. Mago; L. Tabe; R. A. McIntosh; Z. Pretorius; R. Kota; E. Paux; T. Wicker; J. Breen; E. S. Lagudah; J. G. Ellis; W. Spielmeyer (Theoretical and Applied Genetics, 2011)

MRI-guided Thermal Ablation Therapy: Model and Parameter Estimates to Predict Cell Death from MR Thermometry Images - Michael S. Breen; Miyuki Breen; Kim Butts; Lili Chen; Gerald M. Saidel; David L. Wilson (Annals of Biomedical Engineering, 2007)

Mechanistic Computational Model of Ovarian Steroidogenesis to Predict Biochemical Responses to Endocrine Active Compounds - Michael S. Breen; Daniel L. Villeneuve; Miyuki Breen; Gerald T. Ankley; Rory B. Conolly (Annals of Biomedical Engineering, 2007)

Watershed Nitrogen and Mercury Geochemical Fluxes Integrate Landscape Factors in Long-term Research Watersheds at Acadia National Park, Maine, USA - J. S. Kahl; S. J. Nelson; I. Fernandez; T. Haines; S. Norton; G. B. Wiersma; G. Jacobson; A. Amirbahman; K. Johnson; M. Schauffler; L. Rustad; K. Tonnessen; et al. (Environmental Monitoring and Assessment, 2007)

Which women aren’t getting mammograms and why? (United States) - Helen I. Meissner; Nancy Breen; Michele L. Taubman; Sally W. Vernon; Barry I. Graubard (Cancer Causes & Control, 2007)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

Three-Dimensional Registration of Magnetic Resonance Image Data to Histological Sections with Model-Based Evaluation - Michael S. Breen; Roee S. Lazebnik; David L. Wilson (Annals of Biomedical Engineering, 2005)

International system for cytogenetic nomenclature of the domestic horse: Report of the Third International Committee for the Standardization of the Domestic Horse Karyotype, Davis, CA, USA, 1996 - A. T. Bowling; M. Breen; B. P. Chowdhary; K. Hirota; T. Lear; L. V. Millon; F. A. Ponce de Leon; T. Raudsepp; G. Stranzinger (Chromosome Research, 1997)